Oral Submucous Fibrosis: A Review Article on Etiopathogenesis - Tak, J; Gupta, N; Bali, R (Kathmandu University Medical Journal, 2015)
Areca quid chewing related oral mucosal lesions are potential hazard to a large population worldwide. Commercially freeze dried products such as pan masala, guthka and mawa have high concentration of areca nut per chew and appear to cause OSMF more rapidly than by self prepared conventional betel quid that contain smaller amounts of areca nut. The basic constituent of areca nut is either raw or dried or boiled or baked. Diverse agents including lime, tobacco, catechu, cloves, saffron and leaf of piper betel leaves may form a part of formulation. Many of the undesirable aspects of areca nut have been attributed to arecoline. These chemical appear to interfere with the molecular processes of deposition and or degradation of extracellular matrix molecules such as collagen, causing imbalance in the normal process. The most likely events that take place with regards to the above imbalance may be reduced phagocytosis of collagen by fibroblasts, up or down regulation of copper dependent enzyme lysyl oxidase, matrix metalloproteinases and tissue inhibitors of matrix metalloproteinases. It has been postulated that areca nut may also induce the development of the disease by increased levels of cytokines in the lamina propria. Current evidence implicates collagen related genes in susceptibility and pathogenesis of OSMF. The individual mechanisms operating at various stages of the disease- initial, intermediate and advanced–need further study in order to propose appropriate therapeutic interventions.Kathmandu University Medical Journal Vol.12(2) 2014: 153-156